PELATIHAN GOAL SETTING UNTUK MENINGKATKAN EFIKASI DIRI AKADEMIK SISWA - Nyoman Wiraadi Tria Ariani (Faculty of Psychology, Diponegoro University, 2025)
This research aimed to examine the effectiveness of goal-setting training in improving students' academic self-efficacy. The study employed a quantitative approach with a one-group pre-test and post-test design. The sample was selected using purposive sampling and consisted of 12 individuals. Data analysis involved using paired sample t-tests to assess the effectiveness of the intervention by examining the differences between pre-treatment and post-treatment scores. The goal-setting training comprised five sessions, namely: (1) self-analysis, (2) career insights, (3) goal setting and career planning, (4) action planning, and (5) evaluation, all of which aimed to address issues related to the academic self-efficacy of tenth-grade students. The results of the study revealed that goal-setting training did not lead to a significant improvement in the academic self-efficacy scores of the students. The increase in academic self-efficacy scores was observed in only a small subset of the students who participated in the training, and even then, the improvement was modest, only a few points. This outcome may be attributed to the limited openness of some students in fully benefiting from each training session and time constraints, often coinciding with practical lessons. Consequently, students undergoing the training may have experienced a lack of focus during the training sessions. This situation underscores the need for further efforts to enhance the effectiveness of goal-setting training. Potential measures include increasing student engagement, providing more intensive support, or better aligning the training schedule to minimize conflicts with practical lessons.